2018
DOI: 10.1111/1753-6405.12761
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and use of family planning methods among iTaukei women in Fiji and New Zealand

Abstract: Objective: iTaukei women's awareness and practice of family planning methods was investigated in New Zealand and Fiji to ascertain differences in behaviour within the context of changing developmental settings. Methods:The study was cross-sectional in nature and recruited women aged 18 years and over from three suburbs in Suva, Fiji, and five cities in New Zealand.Results: Overall, 352 women participated in the study, 212 in Fiji and 140 in New Zealand. The study found that living in New Zealand was significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In support of this, Daniels and colleagues (2015) found in a large United States sample that 37-41% of children born to women without a high-school diploma were unplanned, compared to 17% of pregnancies for women with at least a bachelor's degree, while Girma and Patton (2015) found that education correlates negatively with fertility. In New Zealand, Cammock et al (2018) found that 79% of iTaukei (an ethnicity indigenous to Fiji) women surveyed who were sexually active were not using any method of contraceptive, and that 22% women under 24 in both Fiji and New Zealand had experienced an unplanned pregnancy. ITaukei contraceptive use was lower in New Zealand than the general population.…”
Section: Drivers For Pasifika and Māori Fertilitymentioning
confidence: 99%
“…In support of this, Daniels and colleagues (2015) found in a large United States sample that 37-41% of children born to women without a high-school diploma were unplanned, compared to 17% of pregnancies for women with at least a bachelor's degree, while Girma and Patton (2015) found that education correlates negatively with fertility. In New Zealand, Cammock et al (2018) found that 79% of iTaukei (an ethnicity indigenous to Fiji) women surveyed who were sexually active were not using any method of contraceptive, and that 22% women under 24 in both Fiji and New Zealand had experienced an unplanned pregnancy. ITaukei contraceptive use was lower in New Zealand than the general population.…”
Section: Drivers For Pasifika and Māori Fertilitymentioning
confidence: 99%
“…Moreover, the reasons also focused on false beliefs, such as the preference for conceiving males, the achievement of honor by having as many children as possible, and considering them as a source of safety for their fathers in the old age stages of their lives [22] as well as a source of income for the family. The surrounding factors transform attitudes into behaviors [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…A woman's age, husband's education, wealth, spousal communication, and favourable attitude toward contraception are all associated with contraceptive usage (Azmat et al, 2015;Muhindo et al, 2015;Sultan et al, 2002). Pacific Island Countries (PICs) appeared as under-researched; however, Cammock et al identified Fijian contraception usage average of 45% nationally, but as low as 22% of them are sexually active women (Cammock et al, 2018). The low level of contraception usage is also associated with the low levels of Knowledge, Attitude and Practice (KAP) of women and their partners (Lincoln et al, 2018).…”
Section: Introductionmentioning
confidence: 99%